2020
DOI: 10.2147/dddt.s221518
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolite Profiling in Anticancer Drug Development: A Systematic Review</p>

Abstract: Drug metabolism is one of the most important pharmacokinetic processes and plays an important role during the stage of drug development. The metabolite profile investigation is important as the metabolites generated could be beneficial for therapy or leading to serious toxicity. This systematic review aims to summarize the research articles relating to the metabolite profile investigation of conventional drugs and herb-derived compounds for cancer chemotherapy, to examine factors influencing metabolite profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Glucuronidation is a key contributor for decreased drug bioavailability, by excretion [ 34 , 35 ]. To evaluate the ability of ( S )-tryptophanol-derived isoindolinones to undergo this Phase II pathway, additional incubations were performed in alamethicin induced-HLM in the presence of nicotinamide adenine dinucleotide phosphate (NADPH) and uridine diphosphate glucuronic acid (UDPGA) co-factors [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucuronidation is a key contributor for decreased drug bioavailability, by excretion [ 34 , 35 ]. To evaluate the ability of ( S )-tryptophanol-derived isoindolinones to undergo this Phase II pathway, additional incubations were performed in alamethicin induced-HLM in the presence of nicotinamide adenine dinucleotide phosphate (NADPH) and uridine diphosphate glucuronic acid (UDPGA) co-factors [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic activity on cancer cells using in vitro models may not reflect in vivo findings, since the latter considers pharmacokinetic and pharmacodynamic variables, such as ligand binding to specific receptors, downstream cascade, involvement of second messengers, water/lipid solubility, bioavailability, first-pass metabolism, and renal excretion [ 57 , 58 ]. Therefore, combining these two types of scientific tools is appropriate for a more complete assessment of a substance with antiproliferative action.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new (phyto)pharmaceutical products includes not only pharmacodynamic discoveries but also essential data about the pharmacokinetics profile, therapeutic window, and pharmacological safety, including systemic and genetic toxicology [ 58 , 59 ]. These assessments allow the exclusion of undesirable drug candidates and save time, material and human resources.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that the PKs of magnolin were not affected by the dosage, regardless of whether it was administered intravenously or orally [164]. The process of drug metabolism is a critical aspect of pharmacokinetics and plays a significant role in drug development [165]. Studies have shown that in rats, magnolin undergoes metabolism to produce 4'-O-desmethyl magnolin, 4"-O-desmethyl magnolin, and their respective glucuronides [166].…”
Section: Pharmacokinetic Featuresmentioning
confidence: 99%